Phase Transition of Glycolipid Membranes Studied by Coarse-Grained Simulations - Kociurzynski, Raisa; Pannuzzo, Martina; Böckmann, Rainer (Langmuir, 2015)
Glycolipids are important components of biological membranes. High concentrations of glycolipids are particularly found in lipid rafts, which take part in many physiological phenomena. This different partitioning and interaction pattern of glycolipids in the membrane as compared to those of phospholipids are likely due to their different chemical structures: the polar regions of glycosphingolipids can be even larger than for their hydrophobic moieties, giving rise to a rich conformational landscape. Here we study the influence of glycosphingolipids galactosylceramide (GCER) and monosialotetrahexosylganglioside (GM1) on the structural and thermodynamic properties of a phospholipid (DPPC) bilayer. Using the method of coarse-grained molecular dynamics simulation we show that both glycolipids increase the phase-transition temperature of phospholipid membranes and that the extent of this increase depends on the headgroup size and structure. GM1 shows a strong tendency to form mixed clusters with phospholipids, thereby stabilizing the membrane. In contrast, GCER is dispersed in the membrane. By occupying the interstitial space between phospholipids it causes a tighter packing of the lipids in the membrane. (Graph Presented).